Comments on "A tyrannosaur trackway at Glenrock, Lance Formation (Maastrichtian), Wyoming" (Smith et al., Cretaceous Research, v. 61, pp. 1–4, 2016). (February 2018) - Ruiz, Javier
Abstract: The paper by Smith et al. (2016) included speed calculations performed from a tyrannosaur trackway at Glenrock, Lance Formation, Wyoming. These authors concluded that tyrannosaurs walked in speeds similar to those obtained for other large theropod, but faster than proposed for hadrosaurids, a potential prey. However, the calculations performed by Smith et al. (2016) suffered from methodological and computational errors, which greatly affected the reported results. Here I show that when speeds are correctly calculated from the Glenrock trackway, the obtained values are clearly (about 50–80 percent) higher than the wrong values quoted by these authors. This support even more a significant speed capability for tyrannosaurs than claimed by Smith et al. (2016).